Single-step green synthesis and characterization of gold-conjugated polyphenol nanoparticles with antioxidant and biological activities - Sanna V (Dove Medical Press, 2014)
Vanna Sanna,1,2 Nicolino Pala,1 Giuseppina Dessì,1 Paola Manconi,1 Alberto Mariani,1 Sonia Dedola,3 Mauro Rassu,3 Claudia Crosio,3 Ciro Iaccarino,3 Mario Sechi1,2 1Department of Chemistry and Pharmacy, University of Sassari, Sassari, Italy; 2Laboratory of Nanomedicine, Department of Chemistry and Pharmacy, University of Sassari, c/o Porto Conte Ricerche, Tramariglio, Alghero, Italy; 3Department of Biomedical Sciences, University of Sassari, Sassari, Italy Background: Gold nanoparticles (GNPs) are likely to provide an attractive platform for combining a variety of biophysicochemical properties into a unified nanodevice with great therapeutic potential. In this study we investigated the capabilities of three different natural polyphenols, epigallocatechin-3-gallate (EGCG), resveratrol (RSV), and fisetin (FS), to allow synergistic chemical reduction of gold salts to GNPs and stabilization in a single-step green process. Moreover, antioxidant properties of the nanosystems, as well as preliminary antiproliferative activity and apoptotic process investigation of model EGCG-GNPs on stable clones of neuroblastoma SH-SY5Y cells expressing CFP-DEVD-YFP reporter, were examined. Methods: The GNPs were characterized by physicochemical techniques, polyphenol content, and in vitro stability. The antioxidant activity of the GNPs was also determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) cation (ABTS) radical-scavenging assays. Stable clones of neuronal SH-SY5Y-CFP-DEVD-YFP were generated and characterized, and cell viability after treatment with EGCG-GNPs was assessed after 72 hours through a 3(4,5-dimethylthiazol-2yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium assay. Activation of the apoptotic pathways was also investigated by Western blot analysis. Results: With a diameter in the size range of 10–25 nm, the obtained nanoparticles (NPs) were found to contain 2.71%, 3.23%, and 5.47% of EGCG, RSV, and FS, respectively. Nanoprototypes exhibited remarkable in vitro stability in various media, suggesting that NP surface coating with phytochemicals prevents aggregation in different simulated physiological conditions. The scavenging activities for DPPH and ABTS were highly correlated with EGCG, RSV, and FS content. Moreover, high correlation coefficients between the ABTS and DPPH values were found for the prepared nanosystems. EGCG-GNPs induce a dose-dependent reduction on SH-SY5Y-CFP-DEVD-YFP cell viability that is likely to involve the activation of the apoptotic pathways, similarly to free EGCG, as suggested by the processing of the CFP-DEVD-YFP reporter. Conclusion: These results prompted us to propose the ecofriendly synthesized EGCG-, RSV-, and FS-based nanogold conjugates as suitable carriers for bioactive polyphenols to be used for the treatment of disorders associated with oxidative stress, including neurodegenerative disorders, cardiovascular disease, and cancer. Keywords: gold nanoparticles, epigallocatechin-3-gallate, resveratrol, fisetin, antioxidant activity, SH-SY5Y-CFP-DEVD-YFP cells